Divergent Nickel-Catalysed Ring-Opening–Functionalisation of Cyclobutanone Oximes with Organozincs - Angelini, Lucrezia; Malet Sanz, Laia; Leonori, Daniele (Synlett, 2020)
The development of a nickel-catalysed strategy for the remote alkylation, arylation, vinylation and alkynylation of nitriles is presented. The methodology uses electron-poor O-Ar cyclic oximes and organozincs as coupling partners. This redox process proceeds through the generation of an iminyl radical and its following ring-opening reaction.
Keywords: radical ring-opening; nickel catalysis; nitrogen radicals; C–C bond formation; alkylation; arylation; vinylation; alkynylation